Towards generic support for distributed information systems - CAHILL, VINNY (IEEE, 1991)
We are concerned with providing support for a range of object oriented programming langauges to be used in multi-user, multi-machine, heterogeneous environments requiring associative access, as well as concurrency and storage management. I n order to operate in this environment the implementations of current object oriented languages must however be extended. Our goal is to provide a generic runtime support system open to a range of programming language implementations and requiring no (or only minor) alterations to each supported language.
Proceedings of the International Workshop on Object Orientation in Operating Systems
International Workshop on Object Orientation in Operating Systems
PUBLISHED
Piscataway, NJ, United States
Keywords: Computer Science